Effectiveness of Using Audio-Visual Media in Improving Students' Memorization of Short Surahs at State Elementary School 053987 Kw.Serapuh - Hawa, Siti; Ariani, Fatimah; Rahimi; Nurhefti; Ferawati, Dian (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to analyze the effectiveness of using audio-visual media in improving the memorization of short surahs of grade IV students of SD Negeri 053987 Kw. Serapuh. Audio-visual media was chosen as a learning aid because it is considered to be able to attract students' attention and make it easier for them to memorize short surahs. This study uses a classroom action research (CAR) method with a quantitative approach. Data were collected through observation, memorization tests, and interviews with students. The results of the study showed that the use of audio-visual media significantly improved students' ability to memorize short surahs. In addition, students also became more enthusiastic and active in the learning process. Thus, audio-visual media can be an effective alternative in learning to memorize short surahs in elementary schools.